Penguatan Kapasitas Aparatur Desa Dalam Pengembangan Inovasi Kebijakan Program Pembangunan Desa Berkelanjutan - Latif, Martitah (Jurnal Pengabdian Hukum Indonesia, 2020)
The focus of this service activity is to provide information (transfer of knowledge) about how the target community, in this case, Selorejo Village officials, Girimarto, Wonogiri, make village fund regulations that underlie the programs and activities for village development. The Selorejo Village Government has a desire to help people in need by assisting in the form of money through savings books for the community in the form of disaster management accounts. The poverty alleviation institution in Selorejo has built through the village budget. However, it has encountered obstacles in its implementation to the community due to a lack of legal rule. The village government hopes that there is a legal instrument to support the Selorejo Village Government policy to create its people's welfare through the social sector. This service results show that the problem of village capacity is a serious concern to be increased in the implementation of new, accountable, and participatory village development programs.